Micronutrient recommendations and policies in Spain: the cases of iodine, folic acid and vitamin D Recomendaciones y políticas de micronutrientes en España: el caso del yodo, ácido fólico y la vitamina D - N. Brito Garrfa; L. Serra Majem (Nutrición Hospitalaria, 2012)
Introducción: As part of the work carried out within the EURopean micronutrient RECommendations Aligned (EURRECA) Network of Excellence in Spain, we conducted a series of semi-structured interviews with decision makers and relevant scientific institutions in the field of nutrition and public health. The information gathered was collated with national relevant official and unofficial documents and subsequently analysed. Aim: To describe the current situation about nutrition policy in Spain, with special focus on the process of setting micronutrient recommendations and the development of subsequent policies. 3 cases will be detailed: iodine, folic acid and vitamin D. Methods: Information from 9 interviews was contrasted with the available official and unofficial documents on micronutrients recommendations setting and subsequent policy applications to help the population to achieve their requirements. Results and discussion: Common topics and themes were identified in the interviews and desk research. They describe a heterogenic picture of isolated initiatives and timid measures regarding micronutrients recommendations and subsequent policy instruments. Several recommendations coexist but none of them is the result of an official request by the government or competent authority. Iodine, folic acid and vitamin D represent the past, the present and the future of public health policy measures on micronutrients in Spain. Despite of some examples, there exist a need for action. Conclusions: Current nutrition strategies are focused on obesity, with little room for micronutrients national measures despite of the opinion of many experts. Regardless of the several nutrients recommendations coexisting nowadays in Spain, there exist the need for a coordinated action in the field of micronutrients recommendations, fostered by the health and nutrition official authorities with financial support and clear terms of reference. Introducción: Como parte del trabajo realizado dentro de la Red de Excelencia EURRECA (EURopean micronutrient RECommendations Aligned) en España, realizamos una serie de entrevistas semi-estructuradas con pensadores e instituciones científicas relevantes en el campo de la nutrición y la salud pública. La información obtenida se cotejó con documentos relevantes nacionales, oficiales y no oficiales, y analizada subsiguientemente. Objetivo: Describir la situación actual de las políticas en nutrición en España, con un interés especial en el proceso de establecer las recomendaciones de micronutrientes y el desarrollo de las políticas subsiguientes. Se detallarán 3 casos: el yodo, el ácido fólico y la vitamina D. Métodos: La información procedente de 9 entrevistas se contrastó con los documentos oficiales y no oficiales disponibles sobre recomendaciones sobre micronutrientes y las aplicaciones de las políticas subsiguientes para ayudar a la población a alcanzar los requerimientos. Resultadosy discusión: En las entrevistas y la investigación de despacho se identificaron temas comunes. Describían un cuadro heterogéneo de iniciativas aisladas y medidas tímidas concernientes a las recomendaciones sobre micronutrientes y los instrumentos políticos subsiguientes. Coexisten diversas recomendaciones pero ninguna de ellas es el resultado de una petición oficial gubernamental o de la autoridad competente. El yodo, el ácido fólico y la vitamina D representan el pasado, el presente y el futuro de las medidas de salud pública sobre micronutrientes en España. Con la salvedad de algunos ejemplos, existe la necesidad de actuar. Conclusiones: Las estrategias actuales en nutrición están focalizadas en la obesidad, con poco espacio para las medidas nacionales en micronutrientes a pesar de la opinión de muchos expertos. Independientemente de las diversas recomendaciones que coexisten hoy en día en España, existe la necesidad de una acción coordinada en el campo de las recomendaciones sobre los micronutrientes, amparada por las autoridades oficiales en nutrición y con apoyo económico y unos términos claros de referencia.